Design and Verification of proposed Operation Modes of LLC Converter - Kandrac, J.; Frívaldsky, M.; Prazenica, M.; Simonova, A. (Elektronika ir Elektrotechnika, 2012)
The subject is a comprehensive research on issues of power electronic converters operating at very high switching frequency. This is a group of inverters applicable particularly in the power supply, respectively automotive products. The main purpose of the use of high switching frequency is a high value of power density and reduced weight and dimension parameters of the device. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2606